PENINGKATAN PRODUKSI DAN PEMASARAN UKM BANDENG PRESTO DI SEMARANG - Anis, Samsudin; Agustina, Titin (Universitas Negeri Semarang, 2017)
The purpose of science and technology activities for the community is to solve the problems faced by IbM partners covering aspects of production, quality and hygiene, busi- ness management, and product marketing. There are two partners of SMEs who are engaged in processing and marketing of milkfish presto in Semarang. To achieve the targets of activities carried out by various methods tailored to the purpose of activities, such as lectures / counseling, demonstrations, direct practice, and mentoring. The results of IbM activities are: 1) Produced a unit of presto fuel-saving fuels maker with a production capacity of at least 30 kg once cook 2) Produced one unit of oven milkfish presto tool that has been cooked;3) Known the nutritional value of milkfish presto (proximate test), among others protein, fat, carbohydrate, calcium, water content, and abui level; 4) Produce a typical presto milkfish recipe production Part I or Partner II that can be widely accepted by consumers; 5) Produce the design and quality of presto milk packaging more interesting; 6) Produced P-IRT permit from Dinas Kesehatan for Partners II; 7) The pattern of business management (bookkeeping, promotion, marketing) of presto milkfish industry is neat and modern